Pengaruh Kpop Idol sebagai Brand Ambassador dan Brand Image terhadap Purchasing Decision pada Produk Korea - Nindhira Annisa Putri Setiadi; Nina Nurhasanah (Lembaga Pengembangan Kinerja Dosen, 2026)
The growing phenomenon of Korean Wave (Hallyu) such as KPOP Idol is used as a marketing strategy by Korean brands to attract the attention of Indonesian consumers, especially the younger generation. This study aims to measure the extent to which the role of K-pop idols as brand ambassadors, brand awareness and brand image on purchasing decisions for Korean products in Indonesia. This research is intended for consumers who know Innisfree skincare products in Jakarta City who are at least 17 years old and fans of Kpop Idol Kim Mingyu as a brand ambassador. This research uses quantitative deductive methods. Conducted with 115 Respondents and data obtained from online questionnaires on Google Forms. This study uses PLS SEM (Partial Least Square Structural Equation Modeling). The results of this study show that Brand Ambassadors help increase Purchasing Decisions, while Brand Image strengthens brand image. Brand Awareness also contributes to a better understanding of Brand Image, but does not directly influence Purchasing Decisions. This shows that marketing strategies for KPOP Idols can shape a strong Brand Image and encourage consumers to make Purchasing Decisions, but Brand Awareness alone is not enough to make consumers make Purchasing Decisions. Companies can use this research to gain a deeper understanding of the use of K-pop idols in marketing strategies, particularly in the Indonesian market. Additionally, this helps Korean brands design more optimal strategies to attract attention and build stronger relationships with Indonesian consumers.